First Principles Calculations and Experiments to Determine the Hydrogenation Process of Cu-Li-Mg - Maria Helena Sousa Soares de Oliveira Braga (2013)
Density Functional Theory (DFT) calculations were performed. They were firstly implemented to optimize the structure and refine the stoichiometry of the only ternary compound, CuLi0.08Mg1.92 of the Cu-Li-Mg system. Furthermore using DFT, several possible structures of CuMg2Hx were optimized. Since most of the hydrides are cubic structures or can be considered as distortions of a cubic structure, we have started calculations for CuMg2Hx (x = 4 - 6) with tetragonal and monoclinic structures, similar to those of the hydrides formed by the nearest neighbors of Cu and Mg in the periodic table: NiMg2H4 and CoMg2H5 (e.g. monoclinic C2/c and tetragonal P4/nmm, respectively). It can be concluded that the most stable configuration corresponds to CuMg2H5 with C2/c structure. We have performed several neutron scattering experiments that are in agreement with the first principles calculations.